Design of AC Drive System for EMUs Exported to Georgia - HE Zhai; ZHANG Qiuhong; YANG Wenzhao; LIU Yeping (机车电传动)
Basic parameters and performance requirements of AC drive system for EMUs exported to Georgia were illustrated. Traction/braking characteristics, main circuit, technical parameters, design concepts and technical features of the drive system were introduced. Various conditions under combined test, loading test and commercial running were summarized. Tests and running results validated the reasonable design and reliability of the system, which showed that the general technical requirements for EMUs could be fully met.